Comparison of 1H-NMR spectra by normalisation algorithms for studying amyloid toxicity in cells. (1st January 2013) - Romano, Rocco; Vilasi, Silvia; Acernese, Fausto; Canonico, Rosangela; Vilasi, Annalisa; Giordano, Gerardo; Barone, Fabrizio
A range of debilitating human diseases is associated with the formation of stable, highly organised, protein aggregates, the amyloid fibrils . Substantial evidence suggests that Prefibrillar Oligomeric Aggregates (PFAs), preceding mature fibrils formation, are the crucial species in the onset of the neuronal degeneration even if with mechanisms to be further cleared. In this work, we show how 1 H-NMR cell spectral analysis methods can prove to be very effective tools to clear the PFAs amyloid cytotoxicity mechanisms. Following the same method shown by Vilasi, we apply a new 1 H-NMR analysis algorithm to identify the metabolites significantly varied in cells incubated with toxic oligomers from the amyloidogenic W7FW14F mutant of apomyoglobin. Our main aim is to confirm the results obtained by Vilasi et al., normalising a set of different data spectra with the new PRICONA algorithm here described, thus contributing to strengthen the general framework of metabolites and proteins involved in cellular amyloid toxicity.